MODELISASI BOOTH STAND PORTABLE MENGGUNAKAN HASIL DEFORMASI BENDA GEOMETRI DENGAN KURVA BEZIER DAN KURVA HERMIT - Juliyanto, Bagus; Hilma Saffira ’Aisyah, Locita; Ubaidillah, Firdaus; Dwidja Purnomo, Kosala (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
A portable booth stand is a versatile tool for selling goods or services. It serves various purposes in trade activities and exhibitions. The portable booth stand consists of four parts: the top part, the support part, the body part, and the wheel part. In the research results, variations are obtained using interpolation and deformation techniques applied to cylinders, rectangular prisms, and spheres, utilizing Bezier and Hermite curves. The portable booth stand is created in two different models, namely model 1 and model 2. The top section is formed by deforming cylinders and rectangular prisms through dilation, translation, and cutting operations. The support section is constructed by deforming cylinders using Bezier curves of degrees n = 7, 8, dan 9, and Hermite curves of degrees m = 2, 3, dan 4. Specifically, for model 1, deformation is achieved using Bezier curves, while for model 2, deformation employs Hermite curves. The body section is built by deforming rectangular prisms using Bezier curves of degrees n = 2, 3, and 4. The wheel section is created by deforming spheres through vertical cutting and translation. Combining these sections results in 36 variations for model 1 and 189 variations for model 2.